Story Grammar Elements and Mental State Terms in the Expression of Enabling Relations in Narratives of Bilingual Preschool Children. Issue 10 (26th November 2021) - Fichman, Sveta; Armon-Lotem, Sharon; Walters, Joel; Altman, Carmit
ABSTRACT: The present research analyzes causal relations between events in the narratives of bilingual preschool children with typical development (BiTD) and with developmental language disorder (BiDLD). The analyses focused on story grammar elements (attempts and goals) and mental state terms between events in Enabling relations as features contributing to narrative discourse coherence. Narratives, collected from 48 bilingual children (14 with DLD) aged 5;06–6;06, were examined for the expression of enabling causal relations in both L1/Russian and L2/Hebrew. Children in both groups showed frequent omission of goals, but they used mental state terms to convey Enabling relations between events across episodes. Coherence is argued to be affected by syntactic, referential, and lexical skills.